Multidisciplinary approach to the treatment of a patient with juxtarenal abdominal aortic aneurysm and renal cell cancer - A. V. Chupin; N. R. Masalimov; T. P. Baitman; A. A. Gritskevich; V. A. Kulbak; I. V. Miroshkina; E. V. Kondratyev; Ya. A. Stepanova; I. E. Timina (Исследования и практика в медицине, 2023)
Currently, strategies for the management of tumor diseases of the urinary tract in combination with cardiovascular pathologies are controversial. In domestic literature, only isolated reports are found concerning the treatment of combined oncological and cardiovascular pathologies, and the global experience is limited to individual clinical observations and small retrospective series, primarily describing the experience of individual centers. The current challenge for specialists is to establish the ideal treatment sequence with regard to the optimal timing of each surgical procedure and the initial priority of treatment, or the possibility of performing them simultaneously. The article presents a case of successful simultaneous surgical intervention for juxtarenal abdominal aortic aneurysm (AAA) and renal cell carcinoma (RCC) of the left kidney. The patient underwent resection of an abdominal aortic aneurysm with the replacement of the left renal artery, resection of the left kidney under pharmaco-cold ischemia, with thrombectomy from the renal vein. The postoperative period proceeded satisfactorily. After 6 months, on the control computed tomography of the abdominal organs with contrast enhancement (CT) of the abdominal cavity with CU, the prosthesis of the abdominal aorta and the left renal artery are functioning. According to color duplex scanning (CDS) of the renal vessels, the blood flow in the left kidney is preserved to the periphery with normal speed indicators. No data on the recurrence of the oncological process were received.